ANALISIS SOSIOLOGI SASTRA PADA NASKAH DRAMA “RT NOL RW NOL” KARYA IWAN SIMATUPANG - Firdaus, Asep; Azzahra, Cinta (Berajah Journal, 2024)
This study aims to present the analysis on the script of the drama "RT Nol RW Nol" by Iwan Simatupang. The script of the drama "RT Zero RW Nol" contains a lot of social problems, social disparities that occur in people's lives, and contains social criticism. Thus, the research method used in the analysis of drama scripts focuses on the sociological approach of literature by revealing the structure of drama scripts as an introduction to literary sociological analysis. The plot and flow in the drama script use a forward plot and the writer analyzes the plot and flow using an act scheme. In the study of literary sociology, the social context of the author in the drama script "RT Nol RW Nol" is represented through the background of Iwan Simatupang as a journalist so that his social position in society is important, which affects the literary work and the background of the creation of the work is because Iwan Simatupang has a high social view and humanistic attitude (humanism). His views and attitudes can be seen in his works that raise many social and humanitarian themes. Literature as a reflection of the times in the analysis of this drama script describes the environmental conditions where the homeless live under the bridge which is concerning. The social function in the drama "RT Zero RW Nol" is represented through a message to the community about the importance of mutual respect for fellow human beings regardless of their existing social status, as well as a means of criticizing the government for the government's indifference and unfair treatment received by the homeless due to social inequality.